Pelaksanaan Hak Retensi Obyek Debitur oleh PT Pegadaian Cabang Biak - Anwar Akbar (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2021)
The purpose of this study was to determine the actions taken by Pegadaian when the debtor defaulted. In addition, to find out various kinds of obstacles in the implementation of retention rights at Pegadaian and efforts to resolve them.The method used in this research is to use a normativejuridical research method. Normative juridical, namely looking at government regulations and legal norms contained in legislation. Then look at the rules that are synchronized hierarchically with each other.